2021
DOI: 10.1186/s40069-020-00438-5
|View full text |Cite
|
Sign up to set email alerts
|

Hydration Model and Evaluation of the Properties of Calcined Hwangtoh Binary Blends

Abstract: Calcined hwangtoh is a pozzolanic material that is increasingly being used as a mineral admixture in the concrete industry. This study shows a hydration model for cement–hwangtoh blends and evaluates the various properties of hwangtoh-blended concrete using reaction degrees of binders. First, a kinetic reaction model is proposed for analyzing the pozzolanic reaction of hwangtoh. The reaction of hwangtoh includes three processes: the initial dormant period, boundary reaction process, and diffusion process. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 34 publications
2
21
0
Order By: Relevance
“…Thermogravimetric analysis (SDT Q600, TA Instruments, USA) was used to characterize the samples cured at each temperature for 28 days to analyze the dehydration and thermal decomposition processes of the reaction phase [34,35]. About 30 mg of powder was placed in the ceramic crucible of the thermogravimetric analyzer and heated from 20 to 1000 • C at a heating rate of 15 • C/min.…”
Section: Thermogravimetric Analysismentioning
confidence: 99%
“…Thermogravimetric analysis (SDT Q600, TA Instruments, USA) was used to characterize the samples cured at each temperature for 28 days to analyze the dehydration and thermal decomposition processes of the reaction phase [34,35]. About 30 mg of powder was placed in the ceramic crucible of the thermogravimetric analyzer and heated from 20 to 1000 • C at a heating rate of 15 • C/min.…”
Section: Thermogravimetric Analysismentioning
confidence: 99%
“…The weight loss at 550–900 °C is mainly the decarburization of CaCO 3 [ 30 ]. The sources of CaCO 3 in the product can be the carbonation generated during the preparation of the specimens and the presence of small amounts of CaCO 3 in the cement raw material [ 20 , 31 , 32 ]. Combined with Table 6 , we found that as the content of biochar increased, the weight loss at 20–300 and 300–550 °C decreased, indicating that the hydration products (CSH, AFt, Mc, and CH) were reduced as a result of the inhibition effect caused by the addition of biochar [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…The hydration heat release curve of the blended paste with different substitution amounts was changed to different degrees than the pure cement paste (C1-C100). Generally, the hydration process of cement can be divided into five periods: the initial period, the induction period, the acceleration period, the deceleration period, and the slow development period [ 33 , 34 ]. The induction period of the paste can be observed in Figure 3 a–c; it was found that the heat release of L2(C95L5) and M6(C92.5M7.5) in the induction stage was higher than that of the control specimen C1(C100), but the F10(C85F15) blended paste was lower than C1(C100).…”
Section: Resultsmentioning
confidence: 99%